ORGANIZATIONAL COMMUNICATION IN SHAPING THE IDENTITY OF FEMALE CADRES BASED ON KOHATI VALUES - Jihan Aqilah Zahra; Muhammad Rafiq Daulay; Nurlailan Maghfiroh Silalahi; Putri Nur Hidayah; Feni Khairifa (OPINI: Journal of Communication and Social Science, 2025)
This study explores how organizational communication shapes the identity of female cadres in Kohati HMI Medan Branch through the value of #KohatiBerprinsip. Using a qualitative approach, data were collected through in-depth interviews with twelve cadres at branch and commissariat levels and analyzed thematically. The findings reveal three key communication channels: structural, cultural, and digital communication. These channels create an integrated ecosystem that supports the internalization of Islamic, intellectual, and women-oriented values, forming the foundation of female cadre identity. The value of #KohatiBerprinsip operates as an identity framework embedded in formal training, leadership practices, and informal narrative interactions. However, challenges remain, including uneven information flow, differing interpretations of values, and digital information fatigue. Overall, organizational communication plays a strategic role in strengthening the identity of female cadres as principled and empowered Muslim women, though improvements in communication design and consistency of value-based narratives are needed.